Photocatalytic Degradation of Erythrosin-B using Cadmium Cobaltite for Water Reuse: Efficiency and Degradation Pathway - Samota, Jayanti; Sharma, Suraj; Bhardwaj, Shipra; Intodia, Kumud (Asian Journal of Chemistry, 2020)
In present work, a photocatalytic degradation of Erythrosin-B has been studied using cadmium cobaltite. The impact of different parameters such as pH, amount of cadmium cobaltite, concentration of Erythrosin-B and light intensity have been observed on the reaction rate. Radical quenching experiments revealed that hydroxyl radicals are primarily responsible for the degradation of Erythrosin-B. The progress of reaction monitored spectrophotometrically and it followed pseudo first-order kinetics. An experimental mechanism is proposed for the photochemical degradation of Erythrosin-B.